PERSUASIVE COMMUNICATION STRATEGIES IN ENHANCING LEARNING MOTIVATION: A STUDY AT AL KAUTSAR AL AKBAR ISLAMIC BOARDING SCHOOL, MEDAN - Rifai, Azbar; ., Muktarruddin (JURNAL SOCIUS, 2024)
Education at Pondok Pesantren Al Kautsar Al Akbar, Medan, faces challenges in encouraging the interest and enthusiasm of male students in studying Hadith. This phenomenon is influenced by factors such as a lack of creativity in teaching methods, the application of harsh disciplinary measures, and a curriculum perceived as monotonous. This study aims to identify the persuasive communication strategies implemented by Ustadz Ali Sati to enhance the learning motivation of male students. The research employs a descriptive qualitative method, collecting data through documentation, interviews, and observation. The findings reveal that Ustadz Ali Sati employs three main persuasive communication strategies: a personal approach to less motivated students, delivering content creatively and interactively, and using language that is easy to understand. These findings demonstrate that effective communication strategies can significantly enhance students' motivation to learn, providing valuable contributions to the development of teaching methods in Islamic boarding schools.